Scabies in an Adolescent with Poor Personal Hygiene - Dian Isti Angraini; Neema Putri Prameswari; Eko Budi Susanto (Faculty of Medicine, Public Health, and Nursing, 2022)
Skin disease is one of the public health problems in developing countries such as Indonesia. One of the common skin diseases is scabies, a parasitic infestation that is highly contagious and can cause significant morbidity. Scabies can cause prolonged itching and excoriation, resulting in secondary infection1.Scabies is a skin disease caused by infestation and sensitization of the parasite, Sarcoptes scabiei var. hominis. Scabies is transmitted through several ways, namely direct contact with the skin or indirectly through clothing, bed linen, mattresses, and toiletries. Symptoms that appear are itching and skin eruptions in the form of papules, nodules, and vesicles due to a hypersensitivity reaction2. People who are infected with scabies can transmit it to others even though they do not show symptoms until the infection is successfully treated and the mites and eggs are destroyed3.